PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANTU MENGATASI BULLYING DI SDN BINTARA III BEKASI - Nur Miswondrima; Eka Naelia Rahmah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2025)
The rise of bullying that has occurred recently in the world of education has become a serious matter. Where bullying at school is a bad act and is strictly prohibited in the world of education. The aim of this research is to find out the role of PAI teachers in helping overcome bullying that occurs at SDN Bintara III Bekasi. This research uses descriptive qualitative research. The results of this research show that the role of PAI teachers is running well, namely as follows: Teacher as educator, teacher as instructor, teacher as guide, teacher as advisor, teacher as role model. Of course, the role of PAI teachers can help overcome bullying that occurs, starting from verbal bullying such as saying rude things, making fun of parents' names and so on, physical bullying seen from things that happen such as grabbing friends' legs, and taking friends' belongings, relational bullying, namely ostracism.